2022
DOI: 10.1021/acs.chemrestox.1c00417
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrite on Formation of Tobacco-Specific Nitrosamines in Electronic Cigarette Liquids and Aerosols

Abstract: Tobacco-specific nitrosamine (TSNA) formation occurred during aerosol generation from select commercial cig-a-like e-cigarette products. To understand the drivers behind the potential formation of TSNAs in electronic cigarette (e-cigarette) aerosols and e-liquids, model e-liquid systems were generated in the lab to demonstrate that nitrite can react with nicotine and minor alkaloids to form TSNAs in e-liquids. In the presence of nitrite and nicotine, TSNA levels in e-liquids increased over time and the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Combining these results with the literature search findings, 34 of the 93 HPHCs were at or above LOQs in ENDS aerosols (Table ). The sources of these 34 quantifiable HPHCs fit into one of three categories: Impurities transferred from e-liquids (alkaloids ). Thermo-degradation products from e-liquid ingredients (CO, ,, propylene oxide , ). Impurities from multiple possible sources, such as forming from pyrolysis, transferring from e-liquid, leaching from components, or contamination (amides, ,,, aromatic amines, ,, caffeic acid, , most carbonyls, ,, most metals, , n-nitrosodimethylamine [NDMA], ,, TSNAs , BAP, ,, all phenols, ,,, benzene, ,, styrene, ,, toluene ,, ). …”
Section: Discussionmentioning
confidence: 99%
“…Combining these results with the literature search findings, 34 of the 93 HPHCs were at or above LOQs in ENDS aerosols (Table ). The sources of these 34 quantifiable HPHCs fit into one of three categories: Impurities transferred from e-liquids (alkaloids ). Thermo-degradation products from e-liquid ingredients (CO, ,, propylene oxide , ). Impurities from multiple possible sources, such as forming from pyrolysis, transferring from e-liquid, leaching from components, or contamination (amides, ,,, aromatic amines, ,, caffeic acid, , most carbonyls, ,, most metals, , n-nitrosodimethylamine [NDMA], ,, TSNAs , BAP, ,, all phenols, ,,, benzene, ,, styrene, ,, toluene ,, ). …”
Section: Discussionmentioning
confidence: 99%
“…The most carcinogenic TSNA variants are nicotine-derived nitrosamine ketone and N-nitrosonornicotine ( 86 ). It has been reported that the detection of TSNAs in ENDS in the form of E-liquids and aerosols and elevated temperature accelerated a process whereby the levels of TSNA in e-liquids increased over time, particularly in the presence of nitrite and nicotine ( 87 ). Meanwhile, Farsalinos et al ( 88 ) showed that the TSNA content in ENDS aerosol was correlated with the content in E-liquid.…”
Section: Discussionmentioning
confidence: 99%
“…5), which have been previously linked to the degradation of TSNAs [4,16,35,36]. In ue-cured tobacco, the glycolysis pathway produces ATP and energy to synthesize NADPH and the equivalent for the degradation of the precursors of N-nitrosamides [35,37], which results in a lower content of nitrosamines and consequently the reduced biosynthesis of TSNAs. In addition, carbon metabolism is highly correlated with nitrogen metabolism in plants [38,39].…”
Section: Discussionmentioning
confidence: 99%